Use and perceived helpfulness of smoking cessation methods: results from a population survey of recent quitters - Perez Donna; Dunlop Sally M; Hung Wai; Cotter Trish (BMC, 2011)
Abstract Background Increasing rates of smoking cessation is one of the most effective measures available to improve population health. To advance the goal of increasing successful cessation at the population level, it is imperative that we understand more about smokers' use of cessation methods, as well as the helpfulness of those methods in real-world experiences of quitting. In this survey of recent quitters, we simultaneously examined rates of use and perceived helpfulness of various cessation methods. Methods Recent quitters (within 12 months; n = 1097) completed a telephone survey including questions relating to 13 cessation methods. Indices of use and perceived helpfulness for each method were plotted in a quadrant analysis. Socio-demographic differences were explored using bivariate and multivariate analyses. Results From the quadrant analysis, cold turkey, NRT and gradual reduction before quitting had high use and helpfulness; GP advice had high use and lower helpfulness. Prescribed medication and online programs had low use but high helpfulness. Remaining methods had low use and helpfulness. Younger quitters were more likely to use unassisted methods such as cold turkey; older or less educated quitters were more likely to use assisted methods such as prescribed medication or advice from a general practitioner. Conclusions The majority of recent quitters quit cold turkey or cut down before quitting, and reported that these methods were helpful. Efforts to influence population smoking prevalence should attempt to provide support and motivation for smokers choosing these methods, in addition to assessing the effectiveness and accessibility of other methods for smokers who need or choose them.